The diagnosis of cancer in thyroid fine needle aspiration biopsy. Surgery, repeat biopsy or specimen consultation? - Stanek-Widera, Agata; Biskup-Frużyńska, Magdalena; Zembala-Nożyńska, Ewa; Śnietura, Mirosław; Lange, Dariusz (Polish Journal of Pathology, 2016)
Fine needle aspiration biopsy (FNA) is the only diagnostic method that allows a preoperative diagnosis of thyroid carcinoma. An unequivocal diagnosis of a malignant change is achievable only in cases in which all cytological criteria of carcinoma are met. The aim of the study was to evaluate the necessity of repeat thyroid FNA in patients with papillary thyroid carcinoma verified on consultative examination (CE). We analyzed cytology reports of thyroid FNA and CE that resulted in the diagnosis of papillary carcinoma. Evaluation of the correlation of the cytological diagnosis with the histopathology report was based on data obtained after the surgery. Between 2010 and 2015 in the Institute of Oncology (IO) there were 184 cancers diagnosed on CE or in thyroid FNA performed primarily in IO. Additionally, 74 patients were subjected to repeat biopsy after confirmation of cancer in CE. Histopathological diagnosis of cancer was obtained in 62 (100%) cases that were doubly confirmed with cytological examination. The remaining 12 patients were operated on outside the institute. From 110 FNA primarily performed in the IO, histopathological verification was achievable in 92 cases, from which 92 (100%) provided a confirmation of cancer, and the remaining 18 patients were operated on outside the institute. High (100%) specificity of cancer diagnosis in FNA established primarily and verified on CE (second independent assessment) indicates that repeat FNA in order to confirm the diagnosis is unnecessary.